2016
DOI: 10.21608/jpp.2016.47087
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Genetic Parameters Using Populations in Faba Bean (Vicia Faba L.)

Abstract: To improve yearlings and high potential yield of faba bean. Six populations P 1 , P 2 , F 1 , F 2 , BC 1 and BC 2 produced from three faba bean crosses , namely (Giza 429 x Giza 674), (Masr 1 x Giza 674) and (Giza 40 x Giza 402)) were conducted during three successive winter seasons 2013/14, 2014/15 and 2015/16. The experiment was conducted at the Experimental Farm., Faculty of Agricultural, Al-Azhar University (Assiut Branch). Recorded six generations mean days to maturity, branches number, number of pods, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
2
4
0
Order By: Relevance
“…This implies greater influence of environmental factors for the phenotypic expression of these traits that make it difficult or practically impossible to exercise selection based on phenotypic performance of the genotypes to improve the traits. In close agreement with this result it was reported that higher PCV than GCV exist for DM and PH (Haridy and El-Said, 2016); for DF, DM and PH (Sekhon et al, 2017), and higher PCV for DF and PH (Hamza et al, 2017).…”
Section: Phenotypic and Genotypic Coefficients Of Variationsupporting
confidence: 89%
See 1 more Smart Citation
“…This implies greater influence of environmental factors for the phenotypic expression of these traits that make it difficult or practically impossible to exercise selection based on phenotypic performance of the genotypes to improve the traits. In close agreement with this result it was reported that higher PCV than GCV exist for DM and PH (Haridy and El-Said, 2016); for DF, DM and PH (Sekhon et al, 2017), and higher PCV for DF and PH (Hamza et al, 2017).…”
Section: Phenotypic and Genotypic Coefficients Of Variationsupporting
confidence: 89%
“…While, the higher PCV values than GCV implies greater influence of environmental factors for the phenotypic expression of these traits that make it difficult or practically impossible to exercise selection based on phenotypic performance of the genotypes to improve the traits (Mesfin et al, 2019). Higher PCV values than GCV were reported for days to 90% maturity and plant height (Haridy and El-Said, 2016); for days to 50% flowering, days to 90% maturity and plant height (Sekhon et al, 2017); for days to 50% flowering and plant height (Hamza et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This implies greater influence of environmental factors for the phenotypic expression of these traits that make difficult or practically impossible to exercise selection based on phenotypic performance of the genotypes to improve the traits. In close agreement with this result, high environmental variance than genotypic variance were reported for days to 90% maturity and plant height [16]. Likewise, high environmental variance reported for days to 50% flowering Genotypes Under Soil Acidity Stress in the Central Highlands of Ethiopia and plant height [14,17].…”
Section: Estimates Of Phenotypic and Genotypic Coefficient Of Variationsupporting
confidence: 67%
“…Genetic advance in absolute unit (GA) and percent of the mean (GAM), was estimated in accordance with the methods illustrated [25]. Genetic advance that is expected from selecting the top 5% of the tested genotypes as percentage of the mean (GAM) was categorized as low (0-10), moderate (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and high (>20). Where, k = selection differential (at 5% selection intensity with value 2.06) σp = phenotypic standard h 2 = heritability; x = Grand mean.…”
Section: Pcv =mentioning
confidence: 99%
See 1 more Smart Citation